Investigating the mediating role of psychological capital in the relationship between the dark tetrad personality and creativity in artists - Seyedeh Arefeh Rezazadeh Yazd; Hamidreza Aqamohammadian Sharbaf (فصلنامه علمی- پژوهشی اصول بهداشت روانی)
Introduction: This research aims to analyze the role of psychological capital in mediating the connection of the dark tetrad personality traits with creativity among artists. Materials and Methods: The statistical population of this descriptive-correlational study consisted all followers of the Telegram messenger channel of the Union of Artists of Khorasan Razavi province-Iran, in which 260 artists were studied. They were selected through the voluntary sampling method. Research instruments included the Torrance Creativity Questionnaire, McGee Psychological Capital Questionnaire, and Yousefi and Imanzad Scale of the personality dark tetrad traits, which provided reliable and valid findings. The research uses a path analysis plan. The data were analyzed using a descriptive and inferential statistics method, Structural Equation Modeling (SEM), SPSS software and the AMOS software. Results: The results demonstrated a significant inverse correlation between the dark tetrad personality traits and creativity mediated by psychological capital among artists. There is also a significant inverse correlation between artists' dark tetrad personality traits and creativity. Besides, there is a deep inverse correlation between the dark tetrad personality traits and the psychological capital of artists. There is also a direct relationship between psychological capital and creativity in artists. Conclusion: It seems that the artists with psychological capital have minor tetrad personality traits and delay immediate impulsive gratification. They endure and self-efficiently attempt to produce and create.